PEMANFAATAN MEDIA SOSIAL TIKTOK SEBAGAI SALAH SATU SARANA PROMOSI PERPUSTAKAAN SMK NEGERI 1 SINGARAJA - I Dewa Made Dwipa Iswara Putra (ACARYA PUSTAKA, 2025)
TikTok has become an effective social media for conveying various information and promoting various services, including libraries. This article aims to find out the reasons for using social media TikTok as a means of promoting the library at SMK Negeri 1 Singaraja, how librarians use social media TikTok as a means of promoting activities at the SMK Negeri 1 Singaraja Library and what impact the promotion of library content via social media TikTok has on vocational school users. Negeri 1 Singaraja. This research uses a qualitative descriptive research method and the technique for determining informants uses purposive sampling. In this research, researchers used observation, interview and document study techniques to collect concrete data. From the research results obtained by researchers, they found that library accreditation was one of the reasons why the SMK Negeri 1 Singaraja library used TikTok as a promotional medium for its facilities and services. Librarians use various features on TikTok to upload various activities in the library and interact with users through available features such as the comments feature. However, there are still challenges in utilizing the TikTok social media, where there is no manpower to manage the social media, so posts on TikTok do not have a fixed schedule and there are still many other TikTok features that have not been utilized optimally. Keywords: Library, Library Promotion, TikTok Social Media